Comparison of Euclidean with Manhattan in K-Means Clustering for Grouping Palm Oil Production in the Province North Sumatra - S Solikhun; Lise Pujiastuti (IJISTECH (International Journal of Information System and Technology), 2022)
North Sumatra is the largest palm oil-producing province in Indonesia. The region of North Sumatra has an extensive area of oil palm plantations compared to other provinces in Indonesia. To produce a good clustering of oil palm production using the K-Means Clustering method, it is necessary to compare several calculation methods to find the shortest distance in K-Means Clustering. This study focuses on comparing Euclidean Distance with Manhattan Distance on K-Means Clustering. To determine the best method of calculating the shortest distance, the researchers looked for the smallest Davies Bouldin Index (DBI). The smallest DBI value is at k=2 0.145. The result of grouping oil palm production in Sumatra province with k=2 is the high group being Asahan, Langkat and North Labuhanbatu regencies, while 30 other regencies/cities are in the low group